STRATEGI PENGINJILAN DALAM MENINGKATKAN MINAT PEMUDA BERIBADAH DI GEREJA KRISTEN KUDUS INDONESIA MUJIZAT TELAGAPUNGGUR - Hutabarat, Johannes; Steven; Sipayung, Andy (JURNAL IMPARTA, 2024)
Regarding strategy, it’is always related to obtaining results or achieving goals, therefore it is important to have an evangelism strategy or discipleship service for church growth. The current situation in service activities and youth worship activities at GKKI Mujizat Telaga Punggur is not good and requires more intensive education what researcher have seen so far. This research uses qualitative methods and the informants in this research are five young people who were able to collect data from interviews. The results of the research found youth problems such as low time and spiritual discipline, responsibility in carrying out service tasks and not yet fully structured guidance in groups of young people. The purpose of this research is to describe how the process of this evangelism strategy influences young people's interest in worshiping at GKKI Mujizat Telaga Punggur, because evangelism is very important for church growth. There are lot of obstacles that hinder young people from attending youth worship at church, apart from the lack of availability of things to support the smooth running of worship as well as inadequate human resources. So there are several evangelism strategy efforts that need to be implemented, there are also forms of increasing interest in worship that need to be implemented and whether the impact of the evangelism strategy is in line with the hopes and plans to be achieved. So that we can find out how the implementation or application of the evangelism strategy offered goes according to plan and has an impact on the ministry and even the growth of the youth population.